P61 Evaluating the impact of an Advancing Clinical Practitioner's role in an Integrated Sexual Health Clinic. (16th June 2022) - Hart, Ellen; Grundy-Bowers, Matthew; Spice, William
Abstract : Introduction: Recommendations have been made to ensure Integrated Sexual Health Services have a workforce with the skill set to meet the populations' health needs and this includes the development of the Advanced Clinical Practitioner (ACP) role. This project was carried out to evaluate the impact a trainee ACP's advancing skill set had at an Integrated Sexual Health Clinic. Methods: Mixed method approach was used with observational data initially gained to provide an overview of conditions nurses refer to doctors and to provide the baseline criteria for the project sample of 32 patients. Patients were then asked to complete a patient satisfaction survey utilising the Likert scale. The trainee ACP and their clinical supervisor also carried out assessments of competence and reviewed clinical records. A survey to evaluate the impact of the role was also given to the trainee ACP's colleagues. Results: Patients were either satisfied or very satisfied with the care they received. No patients would have preferred to be seen by a doctor. The trainee ACP scored consistently higher than other nurses in the skill sets reviewed and in the autonomy of their consultations. Colleagues believed that the role had improved patient care and had impacted positively on clinical workload. Discussion: The advancing clinical skill set of the trainee ACP had a positive impact on both service delivery and patient satisfaction. The ACP role would enable more complex patients to be managed without solely relying on senior doctors. However, further research needs to be carried out into the impact of introducing this role. Self-competence and capability assessment using tool 1= always directly supervised 2= usually directly supervised 3= occasionally directly supervised 4= supervision without direct presence 5= no supervision